2012
DOI: 10.12657/denbio.069.006
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Abies alba seedlings to different site conditions in Picea abies plantations

Abstract: Introduction of silver fir (Abies alba Mill.) as one of the historically important coniferous tree species in Central Europe into allochthonous cultivated forests is an important task for contemporary and future generations of foresters. The aim of our work was to optimize the management of fir in allochthonous cultivated stands of National Park Ceské Švýcarsko formed mainly by Norway spruce (Picea abies /L./Karst.). The effects of light and soil conditions and game on the survival and growth of fir plantation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 28 publications
1
3
0
2
Order By: Relevance
“…Consequently, HDR plasticity, fully arranged through height growth plasticity, occurs. This also confirmed the finding of the independence of D on light intensities in the natural regeneration of other conifers, as Kučeravá et al (2012) [62] found the same for silver fir and Claveau et al (2002) [44] observed the same for four conifer species from a group of five. On the other hand, in this study, only D was tested when there were no available data about radial increment.…”
Section: Discussionsupporting
confidence: 86%
“…Consequently, HDR plasticity, fully arranged through height growth plasticity, occurs. This also confirmed the finding of the independence of D on light intensities in the natural regeneration of other conifers, as Kučeravá et al (2012) [62] found the same for silver fir and Claveau et al (2002) [44] observed the same for four conifer species from a group of five. On the other hand, in this study, only D was tested when there were no available data about radial increment.…”
Section: Discussionsupporting
confidence: 86%
“…However microorganisms associated with silver fir have not been fully studied and recognized, especially in Poland. So far, stand regeneration (Filipiak and Komisarek 2005), eutrophication (Lasota et al 2015), effects of soil properties, and preparation on the growth of trees (Kuceravá et al 2013, Kobala et al 2015, Kormanek et al 2015 Table 1. Taxa occurring in the communities of soil fungi, which share in the collection exceeded 0.01% Dominant taxa are marked in bold.…”
Section: Discussionmentioning
confidence: 99%
“…85-90% Beschattung schlechter als bei mehr Licht (Dobrowolska, 2008;Kupferschmid et al, 2014). In Tannenpflanzungen in der Tschechischen Republik war ein Kronendachöffnungsgrad von 30% optimal (Kučeravá et al, 2013). Im Riesengebirge wurden die besten Wachstumsbedingungen für natürliche Tannenverjüngung unter den relativ lichtdurchlässigen Kronen von Lärche und Waldföhre gefunden, also bei ca.…”
Section: Höhenzuwachsunclassified